EVALUASI POLA REKRUTMEN PEGAWAI NEGERI KABUPATEN KUDUS TAHUN 2010 - Khusnul Khotimah; Purwoko .; Budi Setyono (Journal of Politic and Government Studies, 2013)
The number of games corruption in the recruitment of civil servants in theHoly District has encouraged the author to undertake the study, entitled Evaluation ofEmployee Recruitment Patterns in Kudus Regency in 2010.This study aims to identify and analyze patterns of recruitment in the HolyDistrict Government corruption-free as well as to identify and analyze the factors thatinfluence the recruitment process in the Holy District Government. The data wascollected through interviews and documentary studies at BKD Kudus and follow therecruitment of informants in Kudus Regency. This type of research is descriptiveresearch analysis. Descriptive analysis aimed to investigate in detail the activities andwork of humans and these results may provide recommendation for future purposesThe analysis showed that the pattern of recruitment Kudus less compliancewith BKN No. 9 of 2012 on guidelines for the procurement of the civil servant wherethere are indications of corruption. There are several factors inhibiting the recruitmentimplement, namely: leadership factors; factor rules and regulations; weaksupervision; factor low welfare of civil servants.Recommendations from this study are law enforcement and discipline of civilservants in order to eliminate the factors that become barriers BKD in carrying outthe functions and duties in the recruitment of civil servants.Keywords: Patterns of Recruitment and Employee.